Efficient homing of T cells via afferent lymphatics requires mechanical arrest and integrin-supported chemokine guidance - Rieke Martens (Nature Portfolio, 2020)
Immune cells mostly enter lymph nodes (LN) from blood circulation, but whether afferent lymphatics contributes to LN entry is unclear. Here, the authors show, using a photo-convertible reporter, that T cells in afferent lymphatics frequently enter LN and become arrested in the subcapsular sinus, with chemokines and integrins further guiding their migration in the LN.